STUDY OF SOCIAL-EMOTIONAL DEVELOPMENT: THE IMPACT OF FATHERLESSNESS (THUFULA, 2024)
This problem is motivated by the fact that there are still many children who are fatherless because of divorced parents and fathers who are not present in the development of their social and emotional development have not yet developed. This study aims to find out how the impact of fatherlessness on the social and emotional development of children who have divorced parents, and children whose fathers are not present in development. The subjects of this research were 10 single parents/transferential care parents for early childhood children aged 5-6 years. The results of the research on the impact of fatherlessness on social- emotional development who experienced divorced parents had social-emotional development that was not well developed, children were still able to interact with other people but had a shy, quiet, introverted nature, preferring to be alone. the impact of fatherlessness on the social-emotional development of divorced parents has a social-emotional development that begins to develop the ability to interact with the environment and be cooperative. For the ability to interact with the surrounding environment, to be cooperative, to be tolerant, and to be empathetic well even though it is only limited to family members and closest friends. The findings that researchers found on the impact of fatherlessness on social-emotional development occurred in fatherless children, because of divorced parents and fathers who were not present in development. Children who experience divorced parents are more likely to be hampered by aspects of social-emotional development compared to fatherless children who are missing their parents’ role during the development process.